Critical Success Factors in IT Project Management. Case study on IT Banking Front-end IT System Project in Serbia - Ilic, Milena; Rankovic, Marko; Stojčić, Miroslav; Kastratovic, Edita (Journal of Economic Development, Environment and People, 2019)
The success of project management in organizations depends on the context, that is, on type of organization, type of projects they implement, the environment and the conditions for the realization of projects. What matters to the textual issues of project success is due to a number of factors - type of project, importance for organization, resources, and the like. Insufficient number of organizations successfully managed to implement project manager procedures, while others met with a large number of problems, the resistance of employees first of all, ignorance, lack of resources, bad time management and other issues. Organizations must have an incremental approach to the development and implementation of their project management methodologies, especially when it comes to implementing information technology project, that involve a great deal of human-work, innovation and usually cost a lot, development takes a long time, they are based on the knowledge of new technologies, and their success depends on the people who develop them, and those who will use those IT products and services. This is a great challenge for management in terms of use of information technology, budget and planning, involvement of the project team and establishment of support from the environment. Many IT projects are not implemented successfully because of poor application of project management procedures, lack of stakeholder support, absence of project sponsor etc.